From alarinjo to oniduro: stand-up comedy as a neo-cultural expression in Nigeria (2012)
Comedy (Awada), a treasured genre among the itinerant (Alarinjo) theatre of the Yoruba, has come to have dominant influence on diverse performances in Nigeria. Indeed, it could be argued that contemporary Nigerian stand-up comedy has been largely influenced by the indigenous Alarinjotradition of the Yoruba, which harks back to the turn of the 21st century. Building on Alarinjo as a dominant precursor, the Nigerian stand-up comedy platform, in the last two decades has integrated ethnic, linguistic and religious affiliations to become a bastion of recreation and remuneration transcending the boundaries of the nation-state. Phenomenal though it has been, researchers have hardly traced Nigerian stand-up comedy from its Alarinjoantecedents, it being a dominant source and influence, to its eclectic contemporary state. Therefore, this study, through neo-cultural lens, examines the development from Awada/Alarinjo to Stand-up comedy in Nigeria; with a view to providing a credible understanding of the origin, influences, trends, motifs and forms of the fledgling industry. While acknowledging the complexities inherent in empiricism and positivism, the paper charts a genealogical argument for Nigerian stand-upcomedy beginning with the performances of nameless palace satiric entertainers which are traceable to almost every ethnic group in Nigeria, the diverse comic performances inherent in mask dramaturges, through the ‘de-ritualized’ itinerant troupes among the Yoruba. It connects this with the professional travelling theatre of the Ogunde Tradition that brought the traditional theatres of Nigeria into limelight, the art of Moses Olaiya, and Gbenga Adeboye, the precursor of Yoruba and indeed contemporary stand-up comedy in Nigeria. Linking these with aspects of the art of Alii Baba, Gbenga Adeyinka I, Julius Agwu, Basket Mouth, Gandoki, De Don Klint de Drunk and Mohammed Danjuma among others, stand-up comedy-as a contemporary art- is purposively interrogated. Thus, the paper chronicles the sociological, literary and multicultural metamorphosis of this theatrical and comical form.